RECONSTRUCTION OF DETENTITON REGULATION AGAINST A SUSPECT OR DEFENDANT IN ACCORDANCE WITH CIVIL CODE BASED ON JUSTICE - muhammad khambali (International Journal of Law Reconstruction, 2017)
Detention is a criminal act of deprivation of freedom which is one of the criminal forms stipulated in the Criminal Code. The mechanisms of detention have been organized according to the Criminal Procedure Code. Mistakes in detention can lead to fatalities for many parties including people who execute the detention. The impact of detention on suspects/defendants is not only felt by suspects/defendants, but also it is felt by families of suspects/defendants, communities, and countries.